Toponymy of Celtic Scotland - Kalinina S.A. (SHS Web of Conferences, 2023)
It has long been known that there is a certain link between a geographic locality and its name. The paper attempts to link the history, geography, and culture of Scotland with the names of its cities, homesteads, rivers, streams, mountains, hills, and other localities that are either man-made creations or natural phenomena. Despite covering mere 80,000 km2, Scotland is a unique region. Scotland is almost completely washed by sea, although most of its territory lies on the uplands. Mountains, hills, valleys, rich in diverse vegetation, conjure up an attractive look of Scotland. This very landscape forged the features of Scottish place names, one of the oldest place names on the world map. The paper will touch upon the earliest period when the names of Scottish geographic localities appeared, the period when this amazing country, currently part of the United Kingdom of Great Britain and Ireland, was conquered by the Celtic tribes who penetrated this land in different centuries. First, the author dwells on word-building formants enabling to classify the place names of Scotland as part of the “Celtic” period of language evolution. Some elements including aber, ach, auchter/ochter, bail/baile, barr, blair, coil, dal, gart, inver, mach, pit, tulach , dating back to Celtic language culture, are part of most units of the place-name vocabulary of Scotland and primarily denote natural features of the landscape of the target region.